Public Attitudes Toward Deviant Behavior, 1972: Iowa, New Jersey, and Oregon - Tittle, Charles R. ([Verlag nicht ermittelbar], 1986)
The specific purpose of this study was to gather data concerning individuals' perceptions of the likelihood of being caught and punished for committing various minor offenses. However, this study also provides data on several other topics ranging from the respondent's opinion on the importance of following social norms to self-reports of deviant behavior.